India’s Business Environment and GDP Growth: A Macroeconomic Perspective - Koka, Naveen (Journal of Global Economy, Business and Finance, 2026)
This journal article presents the findings of a comprehensive survey conducted among 143 individuals with various backgrounds and expertise to assess their perceptions of India's business environment and its potential impact on the country's Gross Domestic Product (GDP) growth. The study aims to provide insights into the factors that respondents believe are critical in fostering a conducive business climate for India's economic development.